Use of Google Earth Engine for the estimation and variation of the vegetable cover of the amazon forest generated by anthropic activity in Huepetuhe period 2016 to 2022 - Estrada Zuñiga, Andrés Corsino (2024)
The estimation and variation of the vegetation cover of the Amazon forest generated by anthropic activity in Huepetuhe had the purpose of estimating the loss of vegetation and the deforestation rates for an Amazon forest, the study was carried out using Landsat 8 satellite images, the treatment of the raster images was made using the ERDAS software, the images were subjected to geometric and radiometric corrections, for this purpose control points were taken on the ground, for the analysis four categories of forest degradation were established: Forest with null vegetation with presence of bare soil, forest with sparse vegetation, forest with moderate vegetation and total area of deterioration. The results from the analysis of the multispectral images and the NDVI show that compared to 2016, 30.1 ha increased in the forest category with no vegetation, 28.8 ha in forests with sparse vegetation, 236.9 ha for forests with moderate vegetation and the area of global deterioration increased by 295.8 ha. The annual deforestation rate was 5% (6.02 ha/year) for forests with no vegetation and presence of bare soil and 9% (59.16 ha/year) for global degradation, the coefficient of determination for forests with no vegetation and area naked was R2=0.9704, and for global deterioration of the forest R2=0.957.